2017
DOI: 10.1590/1516-3180.2016.0207091216
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of death by suicide in Brazil and in the United States: descriptive, cross-sectional time series study

Abstract: CONTEXT AND OBJECTIVE: The World Health Organization recognizes suicide as a public health priority. Increased knowledge of suicide risk factors is needed in order to be able to adopt effective prevention strategies. The aim of this study was to analyze and compare the association between the Gini coefficient (which is used to measure inequality) and suicide death rates over a 14-year period (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013) in Brazil and in the United States … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
(51 reference statements)
1
3
0
1
Order By: Relevance
“…The suicide mortality rates found in this study are higher than those verified in the country to date 6 , 25 - 29 , most likely because no previous study has made any correction for the under-reporting of deaths, and only two have used any method of correction for garbage codes 32 , 34 . The decline in these rates in the period studied is compatible with the tendency already demonstrated by the GBD 2015 35 , but it is contradictory to 11 studies which identified an increase in mortality in recent decades 6 , 25 , 26 , 28 - 32 , 34 , 36 , 37 . Seven studies failed to show the proper ASMRs; therefore, the increase in these rates over time might be due only to the process of aging within the Brazilian population 6 , 25 , 28 , 30 , 31 , 34 , 37 .…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The suicide mortality rates found in this study are higher than those verified in the country to date 6 , 25 - 29 , most likely because no previous study has made any correction for the under-reporting of deaths, and only two have used any method of correction for garbage codes 32 , 34 . The decline in these rates in the period studied is compatible with the tendency already demonstrated by the GBD 2015 35 , but it is contradictory to 11 studies which identified an increase in mortality in recent decades 6 , 25 , 26 , 28 - 32 , 34 , 36 , 37 . Seven studies failed to show the proper ASMRs; therefore, the increase in these rates over time might be due only to the process of aging within the Brazilian population 6 , 25 , 28 , 30 , 31 , 34 , 37 .…”
Section: Discussionsupporting
confidence: 64%
“…Seven studies failed to show the proper ASMRs; therefore, the increase in these rates over time might be due only to the process of aging within the Brazilian population 6 , 25 , 28 , 30 , 31 , 34 , 37 . Of the four studies that used ASMRs 26 , 29 , 31 , 36 , only one implemented a correction for mortality garbage codes 31 and two refer to the periods of 1980 to 2005 and 1990 to 2015 26 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…O Brasil possui um produto interno bruto (PIB) que está entre os maiores do mundo. Porém, em contrapartida, apresenta um dos maiores índices de desigualdade social e de renda, com variáveis econômicas que podem influenciar as taxas de suicídio ( 29 ).…”
Section: Discussionunclassified
“…Additionally, the authors detected an inverse relationship between unemployment and the suicide rate, which contradicts the expected correlation rates reported in several other scientific studies 36 . Another study using a time series comparison of suicide deaths in Brazil and the United States showed that the decreasing economic inequality in Brazil was not significantly related to a decrease in the crude suicide rate as hypothesized 37 . An additional comprehensive investigation of the trend in suicide rates conducted in Brazil using data from 1997 to 2015 reported an increase, which is alarming 38 .…”
Section: Discussionmentioning
confidence: 88%